2023
DOI: 10.3389/fsurg.2022.1094973
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative modified Glasgow prognostic score in surgical non-small cell lung cancer: A meta-analysis

Abstract: Background and purposeThe predictive role of modified Glasgow prognostic score (mGPS) for long-term survival in several types of cancers has been well manifested. We supposed that preoperative mGPS might also be associated with long-term survival of operated non-small cell lung cancer (NSCLC) patients. The aim of this meta-analysis was to identify the prognostic value of preoperative mGPS in surgical NSCLC patients.MethodsThe PubMed, Web of Science, EMBASE and CNKI databases were searched for relevant studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Further validation studies are needed to establish the reliable cut-off value of PNI ratio. Second, we did not assess other immunonutritional statuses such as the Controlling Nutritional Status (CONUT) score or the Glasgow Prognostic Score (GPS), which have been reported as prognostic factors in patients with NSCLC undergoing surgical resection [27,28]. However, direct comparison of the perioperative changes in the PNI, CONUT score, and GPS is challenging because the nature of each of these variables is different.…”
Section: Discussionmentioning
confidence: 99%
“…Further validation studies are needed to establish the reliable cut-off value of PNI ratio. Second, we did not assess other immunonutritional statuses such as the Controlling Nutritional Status (CONUT) score or the Glasgow Prognostic Score (GPS), which have been reported as prognostic factors in patients with NSCLC undergoing surgical resection [27,28]. However, direct comparison of the perioperative changes in the PNI, CONUT score, and GPS is challenging because the nature of each of these variables is different.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Meanwhile, the other meta-analysis by Yang et al just focused on NSCLC patients. [ 52 ] Due to the substantial differences in disease biological characteristics and malignant risk between SCLC and NSCLC, we believe that it is necessary to further identify prognostic value of pretreatment mGPS in SCLC, which contributes to the risk evaluation for SCLC patients. Notably, the study by Mao et al reported an opposite association between elevated mGPS and poor OS in the multivariate analysis combining the distance metastasis and mGPS.…”
Section: Discussionmentioning
confidence: 99%
“…mGPS, which has been shown to predict poor prognosis in solid cancers, may be suitable for use in elderly cancer patients as it is also an indicator of inflammation and malnutrition associated with immunosenescence [25,26]. Recently, preoperative mGPS has been reported to be a novel and reliable predictor for overall survival and disease-free survival in surgical non-small cell lung cancer [18]. A meta-analysis of 41 clinical trials involving 18348 patients with gastric cancer found that higher mGPS was associated with poorer overall survival [27].…”
Section: Discussionmentioning
confidence: 99%
“…Despite all these prognostic indicators, novel markers are needed as the response to treatment and clinical course of patients differ. Recently, the modified Glasgow prognostic score (mGPS) in cancer patients has been used as a new indicator to determine the prognosis and survival of patients [16][17][18]. The prognostic value of mGPS was also confirmed in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%